Serum levels of vitamin D and tumour necrosis factor-alpha in adults with metabolic syndrome - Rahamon, Sheu Kadiri; Arinola Olatunbosun, Ganiyu; Charles-Davies, Mabel Ayebatonyo; Akinlade, Kehinde Sola; Olaniyi, John Ayodele; Fasanmade, Adesoji Adedipe; Oyewole, Oyediran Emmanuel; Owolabi, Mayowa Ojo; Adebusuyi, Jane Roli; Hassan, Olufunke Olayemi; Ajobo, Muhammed Babatunde; Adigun, Kehinde; et al. (European Journal of Clinical and Experimental Medicine, 2021)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. Reports continue to show that a significant association exists between serum vitamin D level and metabolic syndrome (MS)-associated inflammation. However, information on the serum levels of vitamin D and alterations in inflammation in different vitamin D status is presently lacking. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. To determine the serum levels of vitamin D and TNF-α, and assess their possible relationship with gender in individuals with MS. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. Sixty adults with MS and 40 controls were enrolled into this case-control study. Serum vitamin D and TNF-α levels were measured and participants stratified into different vitamin D status. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. None of the participants had vitamin D deficiency and the mean vitamin D level was similar in MS compared with the controls. However, TNF-α level was significantly higher in MS compared with the controls. Serum vitamin D level had significant inverse correlation with serum TNF-α level in MS. Also vitamin D level was significantly lower while TNF-α level was significantly higher in female-MS compared with the male-MS. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Adults with MS have elevated TNF-α level which appears to be associated with the serum level of vitamin D. Also, females with MS have low vitamin D level and this may exacerbate the MS-associated inflammation in them.